Are the therapeutic strategies in anorexia of ageing effective on nutritional status? A systematic review with meta‐analysis. Issue 1 (29th August 2018) - Perna, S.; Rondanelli, M.; Spadaccini, D.; Lenzi, A.; Donini, L. M.; Poggiogalle, E.
Abstract: Background: Anorexia of ageing (AA) may be considered as a risk factor for frailty and has an important impact on quality of life, morbidity and mortality. Methods: A systematic review and a meta‐analysis were performed to summarise the results from several trials on the effectiveness of treatments in AA, as associated with depression, sensory impairment of taste and smell, decreased appetite or early satiety, and disability. Eligible studies were required to report baseline and follow‐up values, the mean change (∆‐change) from baseline, and/or the mean difference among intervention groups versus control group, concerning food intake (kcal/daily) and/or nutritional outcomes, such as body weight, body mass index, albumin and Mini Nutritional Assessment. Results: The systematic review included 20 papers based on different therapeutic approaches concerning food intake and/or nutritional outcomes. The results of the meta‐analysis indicate that the interventions for AA have an important impact on body weight [+1.59 kg; 95% confidence interval (CI) = 1.48–+1.71 kg; P < 0.001) and on energy intake (+56.09 kcal; 95% CI = −54.05 to +166.25 kcal; P = 0.32). Regarding secondary outcomes, it was not possible to meta‐analyse the limited amount of data availab le. Conclusions: The different variants of AA need to be defined because diverse therapeutic approaches are available. A more precise definition of the functional impairments associated with AA may allow a more correct decision about the most appropriate therapy to be prescribed. Moreover, this may allow for a more effective performance of the different therapeutic approaches once they are better targeted to the different scenarios of AA.